2004
DOI: 10.4141/p02-114
|View full text |Cite
|
Sign up to set email alerts
|

Leaf absorption, withdrawal and remobilization of autumn-applied urea-N in apple

Abstract: . 2004. Leaf absorption, withdrawal and remobilization of autumn-applied urea-N in apple. Can. J. Plant Sci. 84: 259-264. Six-year-old well-nourished Jonagold/M9 apple (Malus domestica) trees were sprayed 7 d after harvest with a 2% urea solution enriched with 9.9% atom 15 N. Through 3 d of the absorption period, leaves absorbed 19.2% of the intercepted urea 15 N. This low absorption could be in part due to unfavourable conditions, i.e., low temperatures (daily mean ≈5°C) and windy conditions following treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The close correlation between 15 N of these two fractions with 15 N amount in mature leaves provided supporting evidence. Our finding supports the suggestion that urea is hydrolyzed in situ and assimilated into proteins and amino acids before translocation to other organs ( Tan et al., ; Guak et al., ). However, because the soluble fraction, including amino acids and urea, was not further separated, the possibility that the urea was transported out of the mature leaves to other organs could not be completely excluded ( Tan et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The close correlation between 15 N of these two fractions with 15 N amount in mature leaves provided supporting evidence. Our finding supports the suggestion that urea is hydrolyzed in situ and assimilated into proteins and amino acids before translocation to other organs ( Tan et al., ; Guak et al., ). However, because the soluble fraction, including amino acids and urea, was not further separated, the possibility that the urea was transported out of the mature leaves to other organs could not be completely excluded ( Tan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with apples, peaches, and nectarines (Rosecrance et al, 1998;Tagliavini et al, 1998;Guak et al, 2004), foliar N (as urea) applied in autumn was mostly exported to roots and branches for storage, whereas in spring, the N was primarily exported to newly growing tissues. In this study, 15 N accumulation was observed in the new shoots, which is consistent with previous results in tea plants (Ruan and Gerendá s, 2015).…”
Section: Characterization Of Foliar 15 N Allocation From Mature Leavementioning
confidence: 95%
“…However, these results usually came from experiments spraying or smearing the nitrogenous solution on the leaves of fruit trees or other crops, while the spraying of nitrogen fertilizer on leaves, known as foliar fertilization, is an important management method in agriculture [33], in which the effect of nitrogen application is more through infiltration than through penetration into the sub-pores [34]. The nitrogen concentration in PM 2.5 is usually represented by the unit µg/m 3 [35,36] (such as 13.9-14.7 µg m −3 in 2004-2005 from Hangzhou City, China) [37], which is much less than the application concentration in foliar fertilization that usually uses the unit g N [38,39] (such as leaves spraying 0.5-1 g N plant −1 week −1 in a foliar fertilization experiment) [40].…”
Section: Introductionmentioning
confidence: 99%
“…В научной литературе имеются сведения о влиянии некорневых подкормок на накопление, распределение и реутилизацию запасных питательных веществ плодовыми растениями, но они относятся преимущественно к азотному питанию [7,8].…”
unclassified